Genomic characterisation of New Zealand working farm dogs : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Animal Science at Massey University, Manawatū, New Zealand - Smith, Florence (Massey University, 2025)
The majority of working farm dogs in New Zealand belong to either the Huntaway or Heading Dog breeds. These breeds are unique to New Zealand and are vital to efficient livestock farming, yet no large-scale DNA sequencing studies have been conducted on them to date. The Right Dog for the Job project aims to improve the health and performance of the farm dog population by analysing the genetic and phenotypic information from a sample of 2400 Huntaways and Heading Dogs, including 250 whole genome sequences. As the first use of this dataset, this project aimed to characterise the genetic variation in the sample of whole genome sequences. To this end, sequence bioinformatics tools were used to align sequence reads, then call, filter, and annotate 20 million genetic variants. The dataset was intersected with 395 OMIA-reported functional loci to identify 27 previously described Mendelian variants segregating in the population. Five of these (in the SOD1, VWF, CUBN, CLN8, and SGSH genes) were highlighted as compelling candidates for diagnostic selection. Next, the dataset was surveyed for high impact variants segregating within 132 genes previously shown to harbour phenotype causing variants. The aim here was to use variant effect prediction to identify novel causal variants within functionally relevant genes. This analysis yielded nine causal hypotheses (in the CNGB1, ABCA4, CNP, SLC3A1, CCDC66, GLB1, CYP1A2, and STK36 genes) for future association testing. The second stage of the project leveraged a sample of 299 dogs that were genotyped with the AxiomTM Canine HD Array. Of these dogs, 188 had also been whole genome sequenced. A linkage disequilibrium analysis was conducted to identify predictive markers on the array for several of the 27 Mendelian variants, with a view to supporting future marker-assisted selection. Next, the whole genome sequences were used as a reference to impute missing genotypes in the sample of 111 dogs genotyped with only the Axiom SNP chip, expanding the genomic dataset. Finally, GWAS were performed to identify genetic associations with four body size traits of interest: height, length, chest circumference, and muzzle circumference. Height was significantly associated with a region near LCORL, a gene known to regulate body size in various species. Despite representing one of the first analyses of the ‘Right Dog’ research programme, this project has identified genes and variants that should be of immediate practical use to working dog breeders and owners. The project has also helped to generate an extensive genomic dataset that will underpin future research as part of the broader programme, and ultimately contribute to the health, welfare, and performance of New Zealand’s iconic Huntaway and Heading Dog breeds.
Keywords: 310509 Genomics